1995
DOI: 10.1074/jbc.270.13.7029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of SLP-76, a 76-kDa Tyrosine Phosphoprotein Associated with Grb2 in T Cells

Abstract: The activation of protein tyrosine kinases is a critical event in T cell antigen receptor (TCR)-mediated signaling. One substrate of the TCR-activated protein tyrosine kinase pathway is a 76-kDa protein (pp76) that associates with the adaptor protein Grb2. In this report we describe the purification of pp76 and the molecular cloning of its cDNA, which encodes a novel 533-amino acid protein with a single carboxyl-terminal Src homology 2 (SH2) domain. Although no recognizable motifs related to tyrosine, serine/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
273
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 321 publications
(283 citation statements)
references
References 29 publications
8
273
1
1
Order By: Relevance
“…It has been shown that both SLP65 and SLP76 interact via their proline-rich motifs with the SH3 domain of Grb2 (15,24), thereby forming a complex where both proteins have SH2 domains available for binding. We suggest that this "bivalent" mode of binding would substantially increase the avidity of the interaction between Grb2, SLP65/SLP76, and SCIMP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that both SLP65 and SLP76 interact via their proline-rich motifs with the SH3 domain of Grb2 (15,24), thereby forming a complex where both proteins have SH2 domains available for binding. We suggest that this "bivalent" mode of binding would substantially increase the avidity of the interaction between Grb2, SLP65/SLP76, and SCIMP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have previously demonstrated that SHP-1 is constitutively associated with SLP-76 in the mouse immature B cell line, WEHI-231 (27). SLP-76 is a leukocyte-specific cytoplasmic protein comprised of acidic region at the NH 2 terminus containing three tyrosine residues that can be phosphorylated by Syk family PTKs, followed by a proline-rich region and a COOH-terminal SH2 domain (28). This molecule is involved in the regulation of signaling events initiated by TCR (28 -33) and Fc⑀RI (34).…”
mentioning
confidence: 99%
“…Besides its N-terminal SH2 domain, SLP-76 contains a central proline-rich region and multiple C-terminal tyrosines (Jackman et al, 1995). Once phosphorylated, its binds to a variety of molecules including the exchange factor Vav (Tuosto et al, 1996) and other adapters such as Gads, Nck and SLAP-130 (Boerth et al, 2000).…”
Section: Organization Of Fcr Signaling Complexes By Adapter Proteinsmentioning
confidence: 99%